Glioblastoma Multiforme Causing Calvarial Destruction: An Unusual Manifestation Revisited - Gheyi, Vinay; Hui, Ferdinand K.; Doppenberg, Egon M.; Todd, William; Broaddus, William C. (American Journal of Neuroradiology, 2004)
Summary: This report describes invasion of overlying calvaria and soft tissues by a high-grade glioma without macroscopic evidence of dural involvement. The initial radiologic examinations demonstrated a heterogeneous mass in the right frontoparietal region with both extra- and intra-axial components. Inward displacement of the adjacent dura initially prompted consideration for extra-axial lesions such as metastatic lesions, lymphoma, or an aggressive meningioma. The pathologic findings demonstrated a glial cell origin.